Geospatial approach to wetland vulnerability assessment for Northwest Bangladesh - A. B. M. Abu Haider, A. B. M. Abu Haider (2023)
Despite their inestimable environmental significance, wetlands around the world have been disappearing in an alarming way. In the floodplain region like Northwest Bangladesh (NWBD), wetlands are more exposed to numerous pressure factors which have made them susceptible. Assessment of these threats is essential to understand the state of the wetland ecosystem and to develop a suitable management strategy. Exploring different Landsat imageries from 1989 to 2020, the present study has tried to comprehend the physical vulnerability of the wetlands of NWBD. Remote sensing approach of the Modified Normalized Difference Water Index (MNDWI) has been employed to delineate the areal extent and to evaluate the temporal changes of these wetlands in NWBD. The retrieved results have been drawn on to develop the vulnerability index using different statistical manners. Result reveals that between 1989 and 2020 NWBD has lost 57.89% of its total wetland areas which is around 970.34 km2. Retrieved results provide a clear trail of individual spatial and temporal wetland areal coverage fluctuations in NWBD. Moreover, the decreasing trends of indicators imply a very unsustainable hydrological condition in NWBD which could be a big threat to the existence of its wetlands in near future. With some area-specific adjustments, this simple method of vulnerability assessment would help the policymakers to conserve, manage, and restore the wetlands in NWBD and other areas as well.